1982
DOI: 10.1007/bf02774760
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid secretion, serum gastrin and parietal cell histology in hyperthyroidism

Abstract: A decrease in MAO by gastrin stimulation was observed in 13 of 20 hyperthyroid patients. Five of these 13 cases had achlorhydria. The decrease in gastric acid secretion had no relation to the duration of symptoms, serum T3 and T4 levels, serum antithyroglobulin antibody levels and serum antithyroid microsomal antibody levels. Gastroscopy with biopsy was performed in 17 cases. In patients with achlorhydria, macroscopic and histological atrophy was not observed in the body, and parietal cells were present and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For instance, the prior literature showed that some genetic factors, such as HLA, PTPN22 and CTLA4, were associated with GD . Other studies also observed that hyperthyroidism with autoimmune gastritis is usually accompanied with low acid production that may subsequently lead to an overgrowth of intestinal bacteria . Therefore, it is plausible that hyperthyroidism might be one of the potential risk factors for UC, because both UC and hyperthyroidism are polygenic diseases and may share analogous mechanisms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the prior literature showed that some genetic factors, such as HLA, PTPN22 and CTLA4, were associated with GD . Other studies also observed that hyperthyroidism with autoimmune gastritis is usually accompanied with low acid production that may subsequently lead to an overgrowth of intestinal bacteria . Therefore, it is plausible that hyperthyroidism might be one of the potential risk factors for UC, because both UC and hyperthyroidism are polygenic diseases and may share analogous mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…18 Other studies also observed that hyperthyroidism with autoimmune gastritis is usually accompanied with low acid production that may subsequently lead to an overgrowth of intestinal bacteria. [19][20][21] Therefore, it is plausible that hyperthyroidism might be one of the potential risk factors for UC, because both UC and hyperthyroidism are polygenic diseases and may share analogous mechanisms. 2,18,[22][23][24][25][26] Furthermore, genetic pathways and Th2-dominant immunological responses could contribute to the association between UC and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%